Heterogeneity and productivity - Quamrul Ashraf; Oded Galor; Marc Klemp (Brown University, Department of Economics, 2015)
This research explores the effects of within-group heterogeneity on group-level productivity. It establishes that observed genetic diversity of 230 worldwide ethnic groups, as well as predicted genetic diversity of 1,331 ethnic groups across the globe, has a hump-shaped effect on economic prosperity, reflecting the trade-off between the beneficial and the detrimental effects of diversity on productivity. Moreover, the study demonstrates that variations in within- ethnic-group genetic diversity across ethnic groups contribute to ethnic and thus regional variation in economic development within a country.
Keywords: L25; M14; O10; O40; Z10; 330; Heterogeneity; Regional Development; Out-of-Africa Hypothesis; Comparative Development; Genetic Diversity; Nighttime Light Intensity